Efectos de la administración crónica de cocaína (30 mg/kg) sobre la conducta materna y de la administración prenatal de cocaína y de la conducta materna, sobre la conducta emocional y la ingesta de cocaína (30 mg/kg) y agua en ratones adultos. - Santacruz, María del Pilar (Acta Colombiana de Psicología, 2000)
The chronic administration effects of cocaine (30 mg/kg) (s.c.) were analysed in gestation period on the maternal behaviour (M) on female mice and the effects of prenatal chronic treatment of cocaine (30 mg/kg) and the CM (biological mother vs. nurse) in the emotional behaviour and in the cocaine uptake 30 mg/kg and water in the adult female and male mice. 14 females in gestation period were aleatorily assigned into two groups, a one group to daily cocaine application (30 mg/kg) and the second group to saline solution. From the first day to twelve day of pregnancy. After parturition the cross- nursing was made, each mother kept biological young two males and two females, and four fosters young . The EB of young and mother was treated in the 5 week. The first evaluation and the cocaine uptake were not differential because of the experimental treatment. Effects of the prenatal treatment in the emotional behaviour to long term were found (second evaluation) and potencies for the free uptake of cocaine (30 mg/kg) mainly in the females, which were more anxious because of the highest water uptake and the least exploration. The prenatal treatment with cocaine (30 mg/kg) was stronger that the bring up conclusion in the emotionality and the effects to young females more the males.